Australian sports journalism : power, control, and threats - English, Peter (Professor of journalism) (London : Routledge, 2021)
This insightful volume explores the major challenges facing sports journalism in Australia today, discussing how, in an environment dominated by sports organisations and increasing commercial factors, the role of the sports journalist is being severely compromised. By combining quantitative and qualitative responses from 120 sports journalists with previous research and placing these in the theoretical lenses of field and gatekeeping theories, this book provides a comprehensive overview of the field of Australian sports journalism. Topics discussed include ethical questions in reporting on sports, the role of women in sports journalism, and the increased commercialisation of the field, as well as journalists' perceptions on sports organisations and the changing accessfor media. The book also offers suggestions for the future of the industry, and two contemporary conceptual models are developed. Offering important insight into the workings of contemporary sports journalism in Australia, this book is a useful resource for academics and students around the world in the fields of journalism, media, sports and communication.
Chapter 1 -- Australian sports journalism in a global context Chapter 2 -- The field of Australian sports journalism Chapter 3 -- The commercialisation of sports journalism Chapter 4 -- Sports organisations and media dominance Chapter 5 -- Suggestions for the future of sports journalism Chapter 6 -- Contemporary models of sports journalism References Index
OCLC-licensed vendor bibliographic record.
Keywords: Sports journalism -- Australia; LANGUAGE ARTS & DISCIPLINES / Journalism; SOCIAL SCIENCE / Media Studies